Effect of Wearing Different Types of Face Mask to Heat Strain During Physical Activities - Rusdaniaji, Danarwan; Dharmastiti, Rini (TALENTA Publisher, 2021)
There is a concern to use masks during physical activities when exercising and working. Wearing masks during physical activity will pose a risk to physiological changes in the body and human heat strain by the principle of a mask can block the respiratory tract. This study aims to determine how much the human physiological changes quantitatively and qualitatively when using different types of medical masks, cloths and N95. There were 10 respondents as a sample of this study. The results obtained show that the different types of masks to the physiological response of the human body, cloth masks can affect the physiological changes the highest compared to medical masks and N95. The subjective response in the form of thermal comfort, mask sensation, and thermal sensation shows that of the 3 types of masks, the N95 mask is the mask that is the most uncomfortable when worn. The recommendations of the 3 types of masks are medical masks because they affect the slightest increase in the risk of heat stress while the cloth masks have the highest increase in tympanic temperature and Physiological Strain Index.